Hubungan peran orang tua dengan intensitas penggunaan gadget pada anak usia dini di Kabupaten Tapanuli Selatan - Khairani, Fitri; Naria, Evi; Lubis, Ismil Khairi; Koka, Ecia Meilonna; Harahap, Anni Fadhilah; Rangkuti, Intan Maulida; Marpaung, Melini Tatio Enjelika; Daulay, Halomon (Talenta Publisher, 2024)
Nowadays use gadget not only by adults but also used by toddler. The role of parents is needed to monitor and supervise their children when using gadget. This study aims to determine the relationship between the role of parents and the intensity of use gadget in early childhood. This research uses an approach cross sectional. The independent variable in this research is the role of parents, while the dependent variable is intensity of use gadget. The population of this study is parents who have young children with a total of 80 respondents. The sampling technique uses Purposive Sampling Method, accompanied by inclusion and exclusion criteria. Research instrument on parental role and intensity of use gadget using a checklist sheet that has been tested for validity and reliability. Analysis of this research data used Chi-square test. The research results obtained p=0,043 < Â Î± (0,05) which means that Ho is unaccepted or there is relationship between the role of parents and the intensity of use gadgets in early childhood PAUD/TK in South Tapanuli Regency. It is assumed by researchers that this is because there are rules regarding the duration of play gadget when provided with facilities gadget which is accompanied by sanctions if they violate the rules, create a special account for the child in which it has been filtered, or parents have limited the use of internet data on gadget.